Treatment Expectations for CAM Interventions in Pediatric Chronic Pain Patients and their Parents. Issue 4 (2005) - Tsao, Jennie C. I.; Meldrum, Marcia; Bursch, Brenda; Jacob, Margaret C.; Kim, Su C.; Zeltzer, Lonnie K.
Abstract : Patient expectations regarding complementary and alternative medicine (CAM) interventions have important implications for treatment adherence, attrition and clinical outcome. Little is known, however, about parent and child treatment expectations regarding CAM approaches for pediatric chronic pain problems. The present study examined ratings of the expected benefits of CAM (i.e. hypnosis, massage, acupuncture, yoga and relaxation) and conventional medicine (i.e. medications, surgery) interventions in 45 children (32 girls; mean age = 13.8 years ± 2.5) and parents (39 mothers) presenting for treatment at a specialty clinic for chronic pediatric pain. Among children, medications and relaxation were expected to be significantly more helpful than the remaining approaches ( P < 0.01). However, children expected the three lowest rated interventions, acupuncture, surgery and hypnosis, to be of equal benefit. Results among parents were similar to those found in children but there were fewer significant differences between ratings of the various interventions. Only surgery was expected by parents to be significantly less helpful than the other approaches ( P < 0.01). When parent and child perceptions were compared, parents expected hypnosis, acupuncture and yoga, to be more beneficial than did children, whereas children expected surgery to be more helpful than did parents ( P < 0.01). Overall, children expected the benefits of CAM to be fairly low with parents' expectations only somewhat more positive. The current findings suggest that educational efforts directed at enhancing treatment expectations regarding CAM, particularly among children with chronic pain, are warranted.